Butterfly Hug Reduce Anxiety on Elderly - Pria Wahyu Romadhon Girianto; Dhina Widayati; Syahdila Sabrina Agusti (STIKes Patria Husada Blitar, 2021)
The problem that often occurs in the elderly is anxiety. Anxiety can lead to cognitive impairment, mood disorders, and other emotional disabilities. Butterfly Hug is a non-pharmacological therapy to reduce anxiety levels. This study aims to determine the effectiveness of the butterfly hug on the level of anxiety in the elderly. The research design was a pre-experimental design with a one-group pre and post test design approach. The study population was 60 people and a sample of 18 respondents was used using a purposive sampling technique. Anxiety level instrument using the GAI questionnaire. Data analysis using the Wilcoxon test. The results of the pre-test showed that half of the respondents (50.0%) experienced severe anxiety, half of the respondents (50.0%) experienced moderate anxiety. The post-test results showed that half of the respondents (50.0%) experienced moderate anxiety and half of the respondents (50.0%) experienced mild anxiety. p-value 0.003 and = 0.05 (0.003 0.05) meaning that there is an influence of the Butterfly Hug on the level of anxiety in the elderly. The Butterfly Hug is done by gently clapping hands, which gives a comfortable sensation while breathing. This method can activate LHPA, stimulate the hypothalamus and CRH hormone secretion. ACTH is activated and stimulates the production of serotonin and endorphin hormones which make you feel relaxed and safe, so that anxiety decreases. It is recommended to use the Butterfly Hug as an alternative to reduce the level of anxiety in the elderly at UPT PSTW Jombang-Kediri.Â